Supporting Emotional Regulation in Elementary School: Brain-Based Strategies and Classroom Interventions to Promote Self-Regulation (LEARNing Landscapes, 2011)
Before students are able to be successful with academic demands they must be able to regulate their own emotions. Seven kindergarten students at a Title One school outside of Washington, DC participated in a small-group intervention in order to increase their ability to regulate their own emotions. The curriculum for this group was created based on the neurological implications of how the brain processes emotions.
Keywords: emotion regulation; curriculum; brain; emotion; neurological implication; intervention